1998
DOI: 10.1063/1.121033
|View full text |Cite
|
Sign up to set email alerts
|

Growth of epitaxial AlxGa1−xN films by pulsed laser deposition

Abstract: Epitaxial AlxGa1−xN films have been grown on c-cut sapphire substrates at 800 °C and 10−2 Torr N2 by pulsed laser deposition (PLD) using a KrF laser. Throughout the composition range from x=0 to 0.6, the films show epitaxial patterns in reflection high-energy electron diffraction, in agreement with the results from x-ray diffraction. The lattice constants of the films vary linearly with x. The composition dependence of the band gaps of the films deviates from linearity and bows downward. This letter reports th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0
1

Year Published

1999
1999
2021
2021

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(11 citation statements)
references
References 11 publications
1
9
0
1
Order By: Relevance
“…The same shape was observed for Al xGa 1Àx N films with different Al composition. With increasing the Al concentration, the AlGaN peak position shifts towards higher angles showing a decrease of the lattice constant c. Huang et al [19] have found the same behaviour for Al x Ga 1Àx N with Al content varying between 0 and 60%. The variation of the full width at half maximum (FWHM) of the Al x Ga 1Àx N films versus Al content is shown in the inset of Fig.…”
Section: Article In Presssupporting
confidence: 50%
“…The same shape was observed for Al xGa 1Àx N films with different Al composition. With increasing the Al concentration, the AlGaN peak position shifts towards higher angles showing a decrease of the lattice constant c. Huang et al [19] have found the same behaviour for Al x Ga 1Àx N with Al content varying between 0 and 60%. The variation of the full width at half maximum (FWHM) of the Al x Ga 1Àx N films versus Al content is shown in the inset of Fig.…”
Section: Article In Presssupporting
confidence: 50%
“…First, the early findings of an upward bowing [247,248] were generally not duplicated (with the somewhat inconclusive exception of Ref. The second class of materials, which were grown at high temperatures, generally exhibited a strong downward bowing of at least +1.3 eV [142,[253][254][255][256][257][258]. The second class of materials, which were grown at high temperatures, generally exhibited a strong downward bowing of at least +1.3 eV [142,[253][254][255][256][257][258].…”
Section: Alganmentioning
confidence: 99%
“…Early attempts to grow AlGaN alloy utilized ceramic targets prepared from GaN and AlN powder mixtures [100]. Early attempts to grow AlGaN alloy utilized ceramic targets prepared from GaN and AlN powder mixtures [100].…”
Section: Ternary Alloymentioning
confidence: 99%